Economic Growth, Agricultural Output and Tourism Development in Nigeria: An Application of the ARDL Bound Testing Approach - LAWAL, Adedoyin Isola; ASALEYE, Abiola John; ISEOLORUNKANMI, Joseph; POPOOLA, Olabisis Rashidat (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
Drawing from three tourism-growth theories: tourism led growth theory; growth led tourism theory; tourism – growth neutrality theory; and one agriculture-growth nexus theory – agriculture overlapping theory, this study used the autoregressive distributed lag (ARDL) bound testing approach to examine whether or not cointegration exist among economic growth, agricultural output and tourism development in Nigeria. We intend to know what policy instruments need to be manipulated so as to achieve economic growth, increase agricultural output and enhance tourism development. From the results, it is evidence that a two –way cointegration exists between economic growth and agricultural output on the one hand, and between economic growth and tourism development on the other hand. The study also observed that a compelling long run relationship exist between agricultural output and tourism development. To achieve sustainable economic growth, policy makers are advised to pursue heavy investment in the tourism industry, adopts improved farming strategies driven by simple technology among others.